Una Mirada Interseccional sobre la Violencia de Género contra las Mujeres Mayores = An Intersectional Perspective on Gender-based Violence against Older Women - Ibáñez, Jorge Gracia (Oñati Socio-Legal Series, 2015)
Gender-based violence affects all kinds of women, including the older. In these cases two determining characteristics intersect: gender and age, which usually means greater vulnerability for the victims. In this paper both the benefits of a look at the issue from the paradigm of intersectionality and the need of an autonomous theoretical construction of the issue are discussed. The issue of gender violence against older women has characteristics of its own even it´s still connected to forms of violence like gender violence, as a broad category, or family elder abuse. Some public policies from the perspective of intersectionality are also analyzed.